(3GdTGaj aj TQM GdcGajs - (3GdbRhjfj, Ndjd Hf GdZGRj (B, (3J (B1089 (3g`s ((3eMeO Hf eMeO GdGSJQHGPjs)
(3ChdgG (B:s
(3ChdgG(B: (3eTJed Ydi NeS hKdGKjf HGHG Ydi JhMjO GdUGfY GdYGde, aGdeQGO HGdJhMjO gfG GdJfRjg YeG dG jdjb Hg aj UaGJg hCaYGdg JYGdi Cj YeG jSJMjd Ydjg ShGA CcGf hLhOjGs
(3BNQgG (B:s
(3BNQgG(B: (3GdQGHY CHh Ydj GdCTYQj Yf eMeO Hf YHO GdLHGQ Yf UahGf Hf jMji Yf eMeO Hf eQhGf Yf aVjd Hf jSGQ bGd, bdJ dCHj YHO Gddg Ydjg GdSdGe(B: (3fOYh GdfGS Edi gPG GdCeQ (B... (3aCONdg aj gPG GdCeQ WGFkYG Ch cGQkgGs
(3bhHdJ Ydi fSNI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 321s
(3GdPQjYI, L (B13: 5s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdMOjK hGdeUWdMs